(i) "f(x)=4x^4+3x^2+2x-4"
Write "f" in the nested form:
"f(x)=4x^4+3x^2+2x-4= (4x^3+3x+2)x-4= ((4x^2+3)x+2)x-4=(((4x)x+3)x+2)x-4"
For "x=2" calculate the value of the function "f" :
"f(2)=(((4\\cdot 2)2+3)2+2)2-4=((8\\cdot 2+3)2+2)2-4=(19\\cdot 2+2)2-4=40\\cdot 2-4=76"
(ii) "f(x)=2x^4+x^3+3x^2+5x-6"
Write "f" in the nested form:
"f(x)=2x^4+x^3+3x^2+5x-6=(2x^3+x^2+3x+5)x-6=((2x^2+x+3)x+5)x-6=(((2x+1)x+3)x+5)x-6"
For "x=3" calculate the value of the function "f" :
"f(3)=(((2\\cdot 3+1)3+3)3+5)3-6=((7\\cdot 3+3)3+5)3-6=(24\\cdot 3+5)3-6=77\\cdot 3-6=225"
Comments
Dear Rufuson Oyinki, please use the panel for submitting new questions.
Dear Rufuson Oyinki, You are welcome. We are glad to be helpful. If you liked our service, please press a like-button beside the answer field. Thank you!
c). Factorize the following quartic equation, expressing the result as the product of linear factors where possible. (i) f(x) = 2x4 - 3x3 + 2x – 14x2 + 33x – 18
This is fantastic; thanks a lot.
Leave a comment